Pengaruh Debt to Equity Ratio dan Return On Asset Terhadap Praktik Perataan Laba pada Perusahaan yang Terdaftar di Jakarta Islamic Index (JII) Periode 2020-2023 - Puteh, Anwar; Aurellya, Vira (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study was conducted to find out how the effect of debt to equity ratio and return on asset on income smoothing in companies listed in the Jakarta Islamic Index (JII). Data is taken from www.idx.co.id. Data used from 2017 to 2023. The population in this study is 30 companies with a sample of 17 companies. The sampling method used in this study uses a purposive sampling technique. This study uses quantitative data processed with the Eviews 10 application using the panel regression method. The results of the test give the conclusion that the variables debt to equity ratio and return on asset partially do not have a significant effect on income smoothing. Simultaneously, the debt to equity ratio and return on assets also did not have a significant effect on income smoothing for companies listed on the Jakarta Islamic Index (JII).